Clinical significance of RET and RAS mutations in sporadic medullary thyroid carcinoma: a meta-analysis. Issue 6 (June 2018) - Vuong, Huy Gia; Odate, Toru; Ngo, Hanh T T; Pham, Thong Quang; Tran, Thao T K; Mochizuki, Kunio; Nakazawa, Tadao; Katoh, Ryohei; Kondo, Tetsuo
Abstract : There are ongoing debates with respect to the prognostic roles of molecular biomarkers in sporadic medullary thyroid carcinoma (MTC). In this study, we aimed at investigating the prognostic value of RET and RAS mutations – the two most common mutations in sporadic MTCs. A search was conducted in four electronic databases. Relevant data were extracted and pooled into odds ratios (OR), mean differences (MD) and corresponding 95% confidence intervals (CI) using the random-effect model. We used Egger's regression test and visual of funnel plots to assess the publication bias. From 2581 studies, we included 23 studies with 964 MTCs for meta-analysis. Overall, the presence of RET mutation was associated with an elevated risk for lymph node metastasis (OR = 3.61; 95% CI = 2.33–5.60), distant metastasis (OR = 2.85; 95% CI = 1.64–4.94), advanced tumor stage (OR = 3.25; 95% CI = 2.02–5.25), tumor recurrence (OR = 3.01; 95% CI = 1.65–5.48) and patient mortality (OR = 2.43; 95% CI = 1.06–5.57). RAS mutation had no significant prognostic value in predicting tumor aggressiveness. To summarize, our results affirmed that RET mutation is a reliable molecular biomarker to identify a group of highly aggressive sporadic MTCs. It can help clinicians better assess patient prognosis and select appropriate treatment decisions.